Pengaruh Literasi Keuangan, Penggunaan Paylater, Dan Pendapatan Terhadap Perilaku Konsumtif Generasi Z Di Indonesia - Rizma Avizah Saputri; Fathihani; Yanthy Herawaty Purnama (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the influence of financial literacy, paylater usage, and income on the consumptive behavior of Generation Z in Indonesia. The background of this research is based on the increasing use of digital financial services, particularly paylater, and the growing trend of consumptive lifestyles among Generation Z, who are exposed to the convenience of technology and have relatively low financial control. The research uses a quantitative approach with descriptive and causal analysis. The population in this study consists of Generation Z in Indonesia aged 18–27 years who have income and have used paylater services. The sampling technique used was non-probability sampling with the purposive sampling method, and the sample size was 100 respondents. Data were collected using questionnaires and analyzed using SPSS version 26. The analysis included validity tests, reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that financial literacy has a negative and significant effect on consumptive behavior, meaning that the higher the financial literacy, the lower the tendency to act consumptively. Conversely, paylater usage and income have a significant joint influence on Generation Z’s consumptive behavior.